Ipsilateral radiation for squamous cell carcinoma of the tonsil: American Radium Society appropriate use criteria executive summary. Issue 1 (17th October 2020) - Tsai, C. Jillian; Galloway, Thomas J.; Margalit, Danielle N.; Bakst, Richard L.; Beadle, Beth M.; Beitler, Jonathan J.; Chang, Steven; Chen, Allen; Cooper, Jay; Koyfman, Shlomo A.; Ridge, John A.; Robbins, Jared; et al.
Abstract: Background: We conducted the current systemic review to provide up‐to‐date literature summary and optimal evidence‐based recommendations for ipsilateral radiation for squamous cell carcinoma of the tonsil. Methods: We performed literature search of peer‐reviewed journals through PubMed. The search strategy and subject‐specific keywords were developed based on the expert panel's consensus. Articles published from January 2000 to May 2020 with full text available on PubMed and restricted to the English language and human subjects were included. Several prespecified search terms were used to identify relevant publications and additional evidence published since the initial American College of Radiology Appropriateness Criteria Ipsilateral Tonsil Radiation recommendation was finalized in 2012. The full bibliographies of identified articles were reviewed and irrelevant studies were removed. Results: The initial search and review returned 46 citations. The authors added three citations from bibliographies, websites, or books not found in the literature search. Of the 49 citations, 30 citations were retained for further detailed review, and 14 of them were added to the evidence table. Articles were removed from the bibliography if they were not relevant or generalizable to the topic, or focused on unknown primary disease. Several commonly encountered clinical case variants were created and panelists anonymously rated each treatment recommendation. The results were reviewed and disagreements discussed. Conclusions: The panel provided updated evidence and recommendations for ipsilateral radiation for squamous cell carcinoma of the tonsil in the setting of primary radiation‐based therapy and postoperative adjuvant radiotherapy. This committee did not reach agreements for some case variants due to a lack of strong evidence supporting specific treatment decisions, indicating a further need for research in these topics.